Emulating biology: Building nanostructures from the bottom up - Nadrian C. Seeman; Angela M. Belcher (2002)
The biological approach to nanotechnology has produced self-assembled objects, arrays and devices; likewise, it has achieved the recognition of inorganic systems and the control of their growth. Can these approaches now be integrated to produce useful systems?